Analysis An Expected Legal Rights To Think Before Receiving And Rejecting Legacy - Irma Fatmawati (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
In the current system of the economy, the function of the matter is increasingly essential in the facets of human life, primarily that it can be traded regarding the election of properties often disputes. Such is the case of an inheritance arising in a specific circumstance, for example by the death of the heir and the possessions to be inherited, and those who receive the property. In the case of transfer of the right of this heir to the heir then arises the problem of inheritance. Strictly speaking there is no heir without the death. A human being as a member of the community as long as still alive has a place in society with accompanying various rights and obligations to others as well as to objects - objects that are in society. Mutual affect both parties either happiness or misery felt by both parties. If a member of the community at any time dies, there will be a transition of rights and duties or that we are often familiar with the term inheritance as a result of a legal relationship between the deceased and the abandoned family. According to the provisions of the Civil Code (Civil Code) which switched to this essentially all inheritance included also the debts of the estate. This means opening opportunities for debtors or creditors to insist on repaying the obligations of the inherited legacy to the inheritors. Inheritance according to the Civil Code there are often questions, such as when an heir accepts or rejects legacy, the consequences of the heirs receiving or rejecting the inheritance, the extent to which the inheritance rejection may be involved and the form of restoration of the inheritance's rejection.